2020
DOI: 10.3390/pharmaceutics12080748
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Formulations of Artemisinin and Derivatives as Potential Therapeutics for the Treatment of Cancer, Leishmaniasis and Malaria

Abstract: Cancer, malaria, and leishmaniasis remain the deadly diseases around the world although several strategies of treatment have been developed. However, most of the drugs used to treat the aforementioned diseases suffer from several pharmacological limitations such as poor pharmacokinetics, toxicity, drug resistance, poor bioavailability and water solubility. Artemisinin and its derivatives are antimalarial drugs. However, they also exhibit anticancer and antileishmanial activity. They have been evaluated as pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 166 publications
0
15
0
Order By: Relevance
“…Altogether, we developed easy to produce stable nanoparticle dispersions and dried microparticle powder, with a spherical shape, high encapsulation efficiencies, high drug loadings and methods that enable burst or slow release, as needed. The formulations might be applied in diseases where treatment by artemisinins is efficient, for example cancer, [68][69][70] malaria, and schistosomiasis. [9,71] Formulations of other lipophilic drugs using solvent displacement, and water-soluble as well as waterinsoluble drugs using spray drying method might be produced using identical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, we developed easy to produce stable nanoparticle dispersions and dried microparticle powder, with a spherical shape, high encapsulation efficiencies, high drug loadings and methods that enable burst or slow release, as needed. The formulations might be applied in diseases where treatment by artemisinins is efficient, for example cancer, [68][69][70] malaria, and schistosomiasis. [9,71] Formulations of other lipophilic drugs using solvent displacement, and water-soluble as well as waterinsoluble drugs using spray drying method might be produced using identical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pieces of research have reported that it was not only anti-malaria but also an anti-tumor agent. Artemisinin can promote cell death, block cell cycle, prevent angiogenesis, and tumor metastasis ( 214 ). Its protective effect against I/R injury is mainly due to the activation of the NLRP3 inflammasome pathway, but preconditioning with artemisinin preconditioning could significantly suppress NLRP3 inflammasome activation.…”
Section: Cardioprotective Phytochemicals Attenuating Myocardial I/r I...mentioning
confidence: 99%
“…Nanocarriers are usually developed from polymers, lipids/proteins, metals and carbon-based materials. Compared with traditional drug carriers, nanodrug carriers can solve the pharmacological limitations of poor drug resistance, poor bioavailability and poor water solubility [ 95 , 96 ]. Generally, nanocarriers provide a large surface area and can overcome anatomical obstacles [ 97 ].…”
Section: Strategies To Improve Solubility and Bioavailabilitymentioning
confidence: 99%